Evaluation of oral health status and immunological parameters of hospitalized COVID-19 patients during acute and recovery phases: A randomized clinical trial - Cem Peskersoy; Aybeniz Oguzhan; Cagri Akcay; Beyza A. Dincturk; Hulya S.E. Can; Erdinc K. Kamer; Mehmet Haciyanli (Elsevier, 2024)
Background/purpose: It is known that COVID-19 patients show many clinical oral symptoms due to the immunological mechanisms triggered by the virus. Aim of this study is to analyze the antibody response to SARS-CoV-2, and to evaluate the oral health status of hospitalized patients. Materials and methods: 160 patients with COVID-19 confirmed by SARS-CoV-2-specific RT-PCR testing and 160 healthy volunteers (HI) with similar age, gender and systemic status were included to compare the bio-chemical and oral manifestations. Oropharyngeal swab specimens were collected to evaluate the salivary interleukins (IL-1, IL-6, IL-10) and immunoglobulins (sIgA, sIgG, sIgM). Oral findings (DMFT, plaque index, salivary flow rate), socio-demographic information and systemic conditions were also recorded. Chi-square, Mann-Whitney U and Spearman's ratio tests were applied to determine the possible correlations between the factors (P = 0.05). Results: The mean DMFT scores of COVID-19 patients (12.71 ± 7.3) were significantly higher than the HI (7.39 ± 2.8), whereas cases of total or partial edentulism were more common among COVID-19 patients (P < 0.05). While plaque index scores were similar for both groups (P > 0.05), salivary parameters were found statistically different (P < 0.05). Severe and moderate cases showed higher proinflammatory interleukin levels (IL-1 = 68.74 pg/ml, IL-6 = 53.31 pg/ml) amongst all (P < 0.05). While secretory immunoglobulins were almost depleted at baseline, (sIgA = 0.11 mg/ml, sIgG = 0.21 mg/ml, sIgM = 0.08 mg/ml) they reached to threshold levels after 4 weeks. Conclusion: Higher proinflammatory interleukin levels indicated that traces of ongoing "Cytokine Storm" in COVID-19 patients which can also be observed in oral environment. Poor oral hygiene and malnutrition due to edentulism can pave the way for having a severe COVID-19 infection.